Comparison of homotopy analysis method and homotopy-perturbation method for purely nonlinear fin-type problems - Chowdhury, Md. Sazzad Hossien; Hashim, Ishak; Abdulaziz, O. (Elsevier, 2009)
In this paper, the homotopy analysis method (HAM) is compared with the homotopy-perturbation method (HPM) and the Adomian decomposition method (ADM) to determine the temperature distribution of a straight rectangular fin with power-law temperature dependent surface heat flux. Comparisons of the results obtained by the HAM with that obtained by the ADM and HPM suggest that both the HPM and ADM are special case of the HAM.